1998
DOI: 10.1200/jco.1998.16.1.27
|View full text |Cite
|
Sign up to set email alerts
|

CHOP is the standard regimen in patients > or = 70 years of age with intermediate-grade and high-grade non-Hodgkin's lymphoma: results of a randomized study of the European Organization for Research and Treatment of Cancer Lymphoma Cooperative Study Group.

Abstract: CHOP is the standard regimen for patients > or = 70 years of age with stage II to IV intermediate- and high-grade NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
1
8

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(89 citation statements)
references
References 19 publications
3
77
1
8
Order By: Relevance
“…With advances in medical care, particularly with effective chemotherapy, patients with NHL can now live much longer. This survival benefit, documented in numerous clinical trials, [8][9][10][11][12][13][14][15][16][17][18][19][20] has been translated into the community effectiveness according to our population-based study. Patients receiving chemotherapy had a significantly lower risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in medical care, particularly with effective chemotherapy, patients with NHL can now live much longer. This survival benefit, documented in numerous clinical trials, [8][9][10][11][12][13][14][15][16][17][18][19][20] has been translated into the community effectiveness according to our population-based study. Patients receiving chemotherapy had a significantly lower risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The incidence of NHL has been increasing over the last several decades worldwide, [1][2][3][4][5][6][7] and Caucasians have higher incidence and mortality rates of NHL than patients in other ethnic groups. 1,2,5 During this period of time, treatment has improved, particularly with com-bination chemotherapy CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) [8][9][10][11][12][13][14][15][16] and later with the addition of rituximab to CHOP for Bcell NHL since 1998. [17][18][19][20] Although there were several studies that demonstrated ethnic disparities in receiving these treatments, [21][22][23] none of these studies has specifically addressed ethnic disparities in survival and whether these survival differences were due to disparities in treatment, diagnosis, or socioeconomic status (SES) or to other factors in patients with NHL.…”
mentioning
confidence: 99%
“…Only recently has the recommended treatment for primary aggressive NHL in elderly patients shifted from less-intensive therapy to anthracycline-containing regimens. 5,18 Despite CHOP-like initial therapy most older adults will eventually succumb to relapse. Many physicians, however, remain reluctant to utilize the potentially curative approach of HDT and ASCT for relapsed lymphoma due to limited published data in treating an older population with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous investigators have demonstrated that elderly patients with advanced aggressive NHL benefit from standard full-dose CHOP chemotherapy rather than a dosereduced version, although still less than one-third are cured with such primary treatment. 5 At the time of relapse, highdose therapy (HDT) followed by autologous stem cell transplantation (ASCT) has become the standard of care in younger patients, resulting in 20-50% long-term diseasefree survival (DFS). [6][7][8][9][10][11] Many clinicians, however, are reluctant to subject adults over the age of 60 to HDT for relapsed NHL because limited data are available on the efficacy of such therapy in this age group and because of concerns regarding toxicity.…”
mentioning
confidence: 99%
“…Although this CHOP regimen differs from the American programs, the authors acknowledged the difference and noted that this is the regimen that the BNLI was using since 1974 [55]. The results of other randomized clinical trials using this steroid dosage and conducted by the Lymphoma Group of Central Sweden [62], the Swedish Lymphoma Study Group [56], the European Organization for Research and Treatment of Cancer Lymphoma Cooperative Study Group [59], the Dutch Hemato-Oncology Study Group [58], and by the Grupo Argentino de Tratamiento de la Leucemia Aguda and Grupo Latinoamericano de Tratamiento de Hemopaties Malignas [63] are noted in Table 3.…”
Section: Level V: Prednisone 50 Mg/m 2 /Day/days 1-5 (Or Days 1-8)mentioning
confidence: 99%